Pooled thrombin‐activated platelet‐rich plasma: a substitute for fetal bovine serum in the engineering of osteogenic/vasculogenic grafts. (15th June 2015) - Tchang, Laurent A.; Pippenger, Benjamin E.; Todorov, Atanas; Wolf, Francine; Burger, Maximilian G.; Jaquiery, Claude; Bieback, Karen; Martin, Ivan; Schaefer, Dirk J.; Scherberich, Arnaud
Abstract: The use of fetal bovine serum (FBS) as a culture medium supplement in cell therapy and clinical tissue engineering is challenged by immunological concerns and the risk of disease transmission. Here we tested whether human, thrombin‐activated, pooled, platelet‐rich plasma (tPRP) can be substituted for FBS in the engineering of osteogenic and vasculogenic grafts, using cells from the stromal vascular fraction (SVF) of human adipose tissue. SVF cells were cultured under perfusion flow into porous hydroxyapatite scaffolds for 5 days, with the medium supplemented with either 10% tPRP or 10% FBS and implanted in an ectopic mouse model. Following in vitro culture, as compared to FBS, the use of tPRP did not modify the fraction of clonogenic cells or the different cell phenotypes, but increased by 1.9‐fold the total number of cells. After 8 weeks in vivo, bone tissue was formed more reproducibly and in higher amounts (3.7‐fold increase) in constructs cultured with tPRP. Staining for human‐specific ALU sequences and for the human isoforms of CD31/CD34 revealed the human origin of the bone, the formation of blood vessels by human vascular progenitors and a higher density of human cells in implants cultured with tPRP. In summary, tPRP supports higher efficiency of bone formation by SVF cells than FBS, likely by enhancing cell expansion in vitro while maintaining vasculogenic properties. The use of tPRP may facilitate the clinical translation of osteogenic grafts with intrinsic capacity for vascularization, based on the use of adipose‐derived cells. Copyright © 2015 John Wiley & Sons, Ltd.